PPARβ/δ and γ in a Rat Model of Parkinson's Disease: Possible Involvement in PD Symptoms. Issue 5 (May 2015) - Falcone, Roberta; Marilena Florio, Tiziana; Giacomo, Erica Di; Benedetti, Elisabetta; Cristiano, Loredana; Antonosante, Andrea; Fidoamore, Alessia; Massimi, Mara; Alecci, Marcello; Ippoliti, Rodolfo; Giordano, Antonio; Cimini, Annamaria
ABSTRACT Parkinson's disease is one of the most common neurologic disorder, affecting about 1–4% of persons older than 60 years. Among the proposed mechanisms of PD generation, free radical damage is believed to play a pivotal role in the development and/or progression of the disease. Recently, PPARs, a class of transcription factors involved in several pathways both in physiological and pathological conditions, have been linked by us and others to neurodegeneration. Particularly, PPARγ and its ligands have been indicated as potential therapeutic targets for the treatment of several pathological conditions associated with neuroinflammation within the CNS. The anti‐inflammatory function of PPARγ has attracted attention since agonists exert a broad spectrum of protective effects in several animal models of neurological diseases, including psychiatric diseases. On the other hand a detrimental role for PPARβ/δ has been proposed in Alzheimer, being closely related to the decrease of BDNF and Trkfl. On these bases, in this work we used a 6‐OHDA hemi‐lesioned rat model, inducing loss of dopaminergic neurons, to study the effects of the lesion at three time points from the lesion (1, 2, and 3 weeks), in relevant areas of PD motor symptoms, such as substantia nigra and globus pallidus and in the area of reward and mood control, the nucleus accumbens. In particular, it was studied: (i) the expression of BDNF and its downstream signals; (ii) the modulation of PPARs levels. The results obtained indicate the possible use of a dual PPARβ/δ antagonist/PPARγ agonist to counteract primary and secondary signs of PD neurodegeneration. J. Cell. Biochem. 116: 844–855, 2015. © 2014 Wiley Periodicals, Inc.